Polaritons in periodic and quasiperiodic structures - Albuquerque, Eudenilson L. (Elsevier, 2004)
In recent years there have been exciting developments in techniques for producing multilayered structures of different materials, often with thicknesses as small as only a few atomic layers. These artificial structures, known as superlattices, can either be grown with the layers stacked in an alternating fashion (the periodic case) or according to some other well-defined mathematical rule (the quasiperiodic case). This book describes research on the excitations (or wave-like behavior) of these materials, with emphasis on how the material properties are coupled to photons (the quanta of the light or the electromagnetic radiation) to produce mixed waves called polaritons. Clear and comprehensive account of polaritons in multilayered structures Covers both periodic and quasiperiodic superlattices Careful attention to theoretical developments and tools Invaluable guide for researchers in this field Shows developments from the basics to advanced topics.